DESIGN AND DEVELOPMENT OF EARLY HEAT STROKE DETECTION SYSTEM IN MILITARY CROSS COUNTRY BASED ON IoT - Iksan Jaya; Edy Maryanto; Alexander Victor Bukit; Muhamad Zulkifli (JOURNAL ASRO, 2018)
Cross-country military sports are sports that are contested in the military environment asan effort to foster the physical abilities of the Navy's soldiers. The doctrine in the Indonesian Navyforcefully demands every soldier to never give up in every task that is carried out so that in militarysporting events the soldier will spend all of his abilities. In the process of cross-country competitionwith heavy physical activity causing many soldiers who experience heat exhaust (pre heat strokeconditions) continue to force themselves to compete and will continue to become a heat stroke.This is compounded by the distance traveled so that the medical team had difficulty reaching thesoldiers who experienced the incident. Internet of things (IoT) is the idea that all objects in the realworld can communicate with each other as part of an integrated system using the internet networkas a link.By using the IoT platform it is possible to monitor an object continuously and provideanalysis directly without being limited by distance and time. Based on the description above, it isnecessary to design and build an early detection system for the heat stroke of TNI AL soldiers incross-country military sport activities based on IoT (Internet of Thing). This system can help detectpositions and soldiers who will experience heat stroke so that medical treatment can be given earlyto prevent heat stroke.Keywords: Monitoring, Heat Stroke, Cross Country, IoT.